Factors Related to Sanitation of Passenger Ships at Bitung Ocean Harbour - Albert S. T. Teo; Joy A. M. Rattu; Junita M. Pertiwi; Welong S. Surya (e-CliniC, 2022)
Abstract: Ship sanitation is all efforts aimed to environmental factors in ship to break the chain of disease transmission in order to maintain and enhance its health status. The ship's sanitation inspection is intended to issue a sanitation certificate in order to obtain a Sailing Health Permit. This study aimed to analyze the factors related to sanitation of passenger ships that docked at the port of Bitung ocean harbor. This was a quantitative analytical survey study with a cross sectional design. This study was carried out at the Bitung ocean harbor, Bitung, Indonesia from October 2021 to January 2022, on 90 crew members of the Doro Londa Motor Ship anchored at the Port Samudera Bitung. The results showed that there were relationships, as follows: between knowledge of crew members and ship sanitation (p<0.009); between the captain's leadership and ship sanitation (p<0.013); between the role of officers and ship sanitation (p<0.004); and between the crew's knowledge, the leadership of the captain, and the role of the officer with the sanitation of passenger ships anchored at the port of Bitung ocean harbor. The officer's role was the most dominant variable. In conclusion, factors related to ship sanitation are crews’ knowledge, captain leadership, and officers’ role, Keywords: crew knowledge; captain leadership; officer role; ship sanitation Abstrak: Sanitasi kapal adalah segala usaha yang ditujukan terhadap faktor lingkungan di kapal untuk memutuskan mata rantai penularan penyakit guna memelihara dan mempertinggi derajat kesehatan. Pemeriksaan sanitasi kapal dimaksudkan untuk pengeluaran sertifikat sanitasi guna memperoleh Surat Izin Kesehatan Berlayar (SIKB). Penelitian ini bertujuan untuk menganalisis faktor yang berhubungan dengan sanitasi kapal penumpang yang berlabuh di Pelabuhan Samudera Bitung. Jenis penelitian ialah survei analitik kuantitatif dengan desain potong lintang. Penelitian dilaksanakan di Pelabuhan Samudera Bitung, Kota Bitung, Indonesia pada bulan Oktober 202-Januari 2022 terhadap 90 anak buah kapal (ABK) Kapal Motor Doro Londa yang berlabuh di Pelabuhan Samudra Bitung. Hasil penelitian menunjukkan terdapat hubungan antara: pengetahuan ABK dengan sanitasi kapal (p<0,09); antara kepemimpinan nahkoda dengan sanitasi kapal (p<0,013); antara peranan petugas dengan sanitasi kapal (p<0,04); dan antara pengetahuan ABK, kepemimpinan nahkoda dan peranan petugas dengan sanitasi kapal (p<0,05). Peranan petugas merupakan variabel yang paling dominan. Simpulan penelitian ini ialah pengetahuan ABK, kepemimpinan nakhoda, dan peranan petugas merupakan faktor-faktor yang berhubungan dengan sanitasi kapal. Kata kunci: pengetahuan anak buah kapal; kepemimpinan nahkoda; peranan petugas; sanitasi kapal